South Caloocan Housing and Development Complex - Mariano, Joseph Tristan V. (Manila : National University, 2000)
This study shall deal with the development of a community planning and development complex that will support the needs of these families through providing a complete and sufficient amount of facilities in one community that will help develop their social and mental lives and serve model of every community development through the coming years.
Preface -- Acknowledgement -- Dedication -- Chapter I. Introduction -- Chapter II. Review of Related literature -- Chapter III. Research & methodology -- Chapter IV. Design framework -- Chapter V. Design analysis & presentation -- Chapter VI. Conclusion.
Keywords: COMMUNITY COMPLEX